Lava fountain jet noise during the 2018 eruption of fissure 8 of Kīlauea volcano - Gestrich, Julia E.; Fee, David; Matoza, Robin S.; Lyons, John J.; Dietterich, Hannah R.; Cigala, Valeria; Kueppers, Ulrich; Patrick, Matthew R.; Parcheta, Carolyn E. (Frontiers in Earth Science, 2022)
To mitigate hazards of sustained volcanic eruptions that last hours to months or more, real-time monitoring is crucial. Sustained eruptions have been shown to produce a low frequency (infrasonic) form of jet noise. We analyze the lava fountaining at fissure 8 during the 2018 Lower East Rift Zone eruption of Kīlauea Volcano and connect changes in fountain properties with recorded infrasound signals from an array about 500 m from the fountain using jet noise scaling laws and visual imagery. Video footage from the eruption reveals a change in lava fountain dynamics from a tall, distinct fountain at the beginning of June to a low fountain with a turbulent, out-pouring lava pond surrounded by a tephra cone by mid-June. During mid-June, the sound pressure level reaches a maximum, and peak frequency drops. We use jet noise scaling relationships to develop a model that estimates changes in volcanic jet diameter and jet velocity using infrasound sound pressure level and peak frequency. The model estimates a decrease in velocity in mid-June which coincides with the decrease in fountain height. Furthermore, it estimates an increase in jet diameter which can be explained by the larger width of the fountain that resembles a turbulent lava pond compared to the distinct fountain at the beginning of June. The agreement between the infrasound-derived and visually observed changes in fountain dynamics suggests that jet noise scaling relationships can be used to monitor lava fountain dynamics using infrasound recordings.